2021
DOI: 10.1088/1361-6455/abcede
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the high-order harmonic generation from periodic potentials by Bohmian trajectories

Abstract: The recombination processes of the electrons in solid are illustrated by solving the time-dependent Schrödinger equation. The results show that the Bohmian trajectories and the time evolution of the electronic probability density agrees very well, which demonstrates that we can use the Bohmian trajectories to investigate the recombination processes of the electrons in solid. We select the region where the probability density of the electron reached the strongest and the weakest as the initial position of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The movement of atoms in a chemical complex is determined by keeping the temperature, volume and pressure parameters fixed for a set amount of time. The trajectories for atoms and molecules were calculated with respect to Newton's equations of motion for a system of interacting particles, in which the potential energies and forces involving the particles are acquired through inter atomic potentials and molecular mechanic force fields (87)(88)(89).…”
Section: Molecular Dynamics Simulation Studiesmentioning
confidence: 99%
“…The movement of atoms in a chemical complex is determined by keeping the temperature, volume and pressure parameters fixed for a set amount of time. The trajectories for atoms and molecules were calculated with respect to Newton's equations of motion for a system of interacting particles, in which the potential energies and forces involving the particles are acquired through inter atomic potentials and molecular mechanic force fields (87)(88)(89).…”
Section: Molecular Dynamics Simulation Studiesmentioning
confidence: 99%
“…[21][22][23] Furthermore, the model potential has been widely used to study solid HHG by solving the time-dependent Schrödinger equation (TDSE) based on the single active electron approximation. [24][25][26][27][28] Lu et al employed the model potential to intuitively study the dynamic process of HHG in solids via time-dependent population imaging. [24] Dixit et al discussed the impact of vacancy defects in solid HHG, which can broaden the energy cutoff of the harmonic spectrum.…”
mentioning
confidence: 99%
“…[27] Liu et al demonstrated the applicability of Bohmian trajectory analysis in investigating the recombination process in solid HHG. [28] In a word, researchers have demonstrated the intricate electron dynamics present in solid HHG based on the one-dimensional monochromatic periodic potential.…”
mentioning
confidence: 99%
“…As we know, the move processes of the electrons in a solid can be observed by Bohmian trajectories [39]. Although the solution process is based on classical mechanics (eq.…”
mentioning
confidence: 99%